The Ideality of Implementing Administrative Sanctions Against Environmental Damage - Muhammad Rizky Akbar Ismail; Lego Karjoko (Faculty of Law, University of Merdeka Malang, 2023)
Based on the Government Regulation in Lieu of Law, it has reduced and changed the nomenclature for the imposition of administrative sanctions against environmental pollution and damage. As regulated in the Implementation of administrative sanctions from the instrument, five points are regulated by the government sanctions instrument. This article uses normative research methods with statutory and analytical approaches. Using primary and secondary data types using deductive logic analysis methods. The results of this study indicate that there is a change in administrative sanction arrangements, especially in administrative fines, where there is no specific indicator in providing the amount of fines. The revocation of business licenses is certainly in line with Good Governance, which lies in legal certainty, effectiveness, and efficiency. This is because the government has full responsibility for the legal position that is made to be implemented as fairly as possible. In addition, the government plays an active role in maximizing administrative law instruments wisely and responsibly.How to cite item: Ismail, Muhammad Rizky Akbar, and Lego Karjoko. â€œIdeality of Implementation Administrative Sanctions Against Environmental Damage in Indonesia.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023): 200-211. DOI: 10.26905/idjch.v14i2.10420.